Analisis Penentuan Daerah Pusat Pertumbuhan/Pelayanan di Wilayah Kepulauan Maluku - Muhammad Imam Z Bin Umar; Fahrudin Ramly; Izaac Tony Matitaputty (Fakultas Pertanian, Universitas Pattimura, 2021)
Determining an area to be a center of growth or service is very important and is influenced by its hinterland area. The development of an area as a growth/service center is determined by its readiness to become a growth center area. This study aims to determine the regencies/cities that can be considered feasible as growth centers or services in Maluku Province, especially in Ambon, Seram, and Buru islands. The analytical method used is the Scalogram and the Marshal Centrality Index. The results of the study showed that of the six research areas, Ambon City is still the center of growth or service in this area, while Central Maluku Regency can be an alternative area in the development of the Maluku region in the future.